Overview of LOX-1 Gen 3'UTR188C/T Polymorphism in Medan, Indonesia - Shahrul Rahman; Harun Al Rasyid (PT FORMOSA CENDEKIA GLOBAL, 2026)
Lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1) is categorized under the class E scavenger receptor subgroup. To date, seven distinct polymorphisms have been characterized within the LOX-1 gene, including the 3'UTR188C/T variant. This investigation clinical trial enrolled 35 volunteer subjects (mean age 43 ± 4.6 years, consisting of 27 females and 8 males). Deoxyribonucleic acid (DNA) was extracted from peripheral blood leukocytes employing the standard salting-out methodology. Genotyping of the LOX-1 3′UTR188CT variant was performed using Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP). Digestion with the RsaI restriction enzyme yielded two fragments (184 bp and 23 bp) corresponding to the C allele, and a single intact 207 bp fragment corresponding to the T allele. The restricted DNA fragments were subsequently visualized via ethidium bromide staining. Genotypic analysis of the LOX-1 gene revealed that the CC genotype was present in 15 participants (43%), the CT genotype in 17 participants (49%), and the TT genotype in 3 participants (8%). Out of the 35 subjects, the T allele was detected in 23 individuals (33%), whereas the C allele was highly predominant, appearing in 47 individuals (67%). In conclusion, our investigation demonstrates that the heterozygous CT genotype is the most prevalent variant within this study cohort, and the frequency of the minor T allele is significantly lower than that of the major C allele.